2020
DOI: 10.3390/nu12082188
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and the Risk of Prostate Cancer: A Dose-Response Meta-Analysis

Abstract: Alcohol is widely consumed and is known as a major risk factor for several types of cancers. Yet, it is unclear whether alcohol consumption is associated with the risk of prostate cancer (PCa) or not. We conducted linear and non-linear dose–response meta-analyses of cohort studies on alcohol consumption and PCa risk by types of alcohol (total, wine, beer, and liquor) and PCa (non-aggressive and aggressive). Pubmed and Embase were searched through April 2020 to identify relevant studies. Summary relative risk (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
(86 reference statements)
0
17
1
8
Order By: Relevance
“…Conflicting results have been reported when considering the association between alcohol consumption and PCa. While a significant dose-risk relationship between alcohol intake and aggressive PCa has been proposed starting at low intake level for liquor but at higher doses for wine [73,74], moderate red wine consumption had a protective effect, reducing the risk by 12% [75].…”
Section: Environmental and Occupational Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting results have been reported when considering the association between alcohol consumption and PCa. While a significant dose-risk relationship between alcohol intake and aggressive PCa has been proposed starting at low intake level for liquor but at higher doses for wine [73,74], moderate red wine consumption had a protective effect, reducing the risk by 12% [75].…”
Section: Environmental and Occupational Exposurementioning
confidence: 99%
“…Compared with no meat consumption, >10 g/d of very-well-done meat was associated with a 1.4-fold increased risk of PCa (95% CI: 1.05-1.92) 2. Total, red, or white meat intake was not associated with prostate cancer risk Sugar-sweetened beverages Llaha et al (2021) [72] Meta-analysis 4 458 056 Random effects showed a significant positive association between intake of sugar-sweetened beverages and fruit juices, and PCa risk (RR: 1.18, 95% CI: 1.10-1.27 and RR: 1.03, 95% CI: 1.01-1.05, respectively) Alcohol Zhao et al (2016) [73] Meta-analysis NA Adjusted RR estimates indicated an increased risk of PCa among low-(RR: 1.08), medium-(RR: 1.07), high-(RR: 1.14), and higher-volume (RR: 1.18) drinkers compared with abstainers Hong et al (2020)[74] Meta-analysis NA 1. Total alcohol consumption was not associated with PCa 2.…”
mentioning
confidence: 99%
“…Our findings persisted after adjustment for previously identified risk factors for prostate cancer incidence and mortality, i.e., age, SES variables [22], and comorbidities related to tobacco smoking and alcohol [30][31][32]. Even though low SES, tobacco smoking, and excessive alcohol use are all associated with DUD [17,[25][26][27][28][29]38], these variables could not entirely explain the increased prostate cancer mortality among men with DUD.…”
Section: Discussionmentioning
confidence: 65%
“…Several SES factors, for example neighborhood deprivation, being unmarried, or having low income or educational attainment, have been associated with increased prostate cancer risk and worse prostate cancer prognosis [22]. Lifestyle factors such as tobacco smoking and negative alcohol-related consequences are overrepresented among people with low SES [23,24] or DUD [25][26][27][28][29], and are also identified as risk factors for prostate cancer and poor prognosis in some studies although the associations are heterogeneous [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant dose-response relationship for current drinkers (Zhao et al, 2016). In a recent linear and non-linear dose-response meta-analyses of cohort studies on alcohol consumption and prostate cancer risk by types of alcohol and type of prostate cancer (non-aggressive and aggressive), Hong et al (2020) found that total alcohol consumption was not associated with aggressive and non-aggressive prostate cancer, while wine was not significantly associated with non-aggressive prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 94%